Digital media research: Will it continue to be a trend in the future? - Rianto, Puji (Jurnal Komunikasi, 2025)
The articles published in Jurnal Komunikasi Vol. 19 No. 2 April 2025 continue the trend observed in studies featured in recent editions of Jurnal Komunikasi. These studies reflect a growing interest in new media or digital media research across various objects, approaches, and perspectives amidst a steady decline in attention toward traditional media such as radio, television, and newspapers. Although television remains an important source of information and entertainment in Indonesia and was even highly popular several decades ago (Heryanto, 2015), researchers now appear more inclined to focus on internet-based digital media studies. This interest is inseparable from the increasingly prominent presence of digital media platforms over recent years not only in Indonesia but also globally (Twenge et al., 2019). For illustration, data released by the Pew Research Center indicate that the majority of Americans use YouTube and Facebook; meanwhile Instagram, Snapchat, and TikTok are predominantly used by those under thirty years old